PHYSIOLOGICAL AND PATHOLOGICAL FEATURES OF THE HEMOSTASIS SYSTEM (International journal of artificial intelligence, 2026)
The hemostatic system is a complex biological mechanism responsible for maintaining blood fluidity under physiological conditions and preventing excessive blood loss following vascular injury. It involves coordinated interactions between vascular responses, platelet activation, plasma coagulation factors, and fibrinolytic processes. Disturbances in the balance between these mechanisms may lead to hemorrhagic complications or pathological thrombosis.The aim of this study is to analyze the physiological and pathological features of the hemostatic system and summarize current knowledge regarding the mechanisms regulating coagulation, platelet activity, and fibrinolysis. Particular attention is given to molecular and cellular mechanisms of thrombus formation and the role of endothelial dysfunction, inflammatory responses, and immune mechanisms in the development of hemostatic disorders.Understanding the mechanisms of hemostasis is essential for improving diagnostic approaches and developing effective strategies for the prevention and treatment of thrombotic and hemorrhagic diseases.